Recurrent malignant pheochromocytoma with lymph nodal metastasis in a child: A rare case - Jayesh Mittal; Ramanitharan Manikandan; Lalgudi Narayanan Dorairajan; Pampa Ch Toi (Wolters Kluwer Medknow Publications, 2017)
Malignant pheochromocytoma in children manifesting as local recurrence with multiple lymph nodal metastasis is a rare entity. We report a case of a 14-year-old child with recurrent sporadic malignant pheochromocytoma presenting 8 years after primary surgery with retroperitoneal lymphadenopathy. The child underwent excision of the tumor along with retroperitoneal lymphadenectomy. Histopathology confirmed pheochromocytoma with extensive lymph node metastasis. The patient has no signs of disease recurrence till date. This report supports the long-term follow-up and aggressive surgical approach to remove all foci of tumor in recurrent pheochromocytoma.